THE INFORMATION SOCIETY: a systematic review of the literature - Lopes, Alex Ciarcia; de Souza, Crediano Maria (Revista Interface Tecnológica, 2023)
Information can be defined as a set of data or facts that have been organized and processed in a meaningful way to generate meaning or meaning. Being an essential part of a decision-making and/or problem-solving process in many fields, including business, science, technology, medicine, and many others. In essence, information is represented or described from something that is considered useful. In this context, it is part of the day-to-day of companies, presenting itself as a subject present in several published works due to its importance and necessity in the business environment. The objective of this research is to carry out a systematic review of the literature on the information society. The adopted research method was based on the Systematic Literature Review technique. At the end, it can be seen that the Information Society theme is very comprehensive, demonstrating the importance of the relationship with ICT and the benefits that it can bring; It is worth mentioning that, in the same way, the negative face is demonstrated, highlighting the problems caused by false information.